FEATURES OF TRANSFRONTIER DIFFUSION OF INNOVATIVE TECHNOLOGIES - A. S. Grigoryeva (Модернизация, инновация, развитие, 2015)
In the article the process of transfrontier diffusion of innovative technologies is considered on the example of RFID technology promotion in Russia and Germany. Moreover, are exposed the factors, which prevent successful development of it. Subjects, which are able to improve the situation and increase the competitiveness of native innovative decisions on world market, are determined.